Students' responses to Maria Grzegorzewska's Letters to a Young Teacher - Marta Krasuska-Betiuk; Monika Kupiec (Studia z Teorii Wychowania)
The problem of the article is situated in the field of pedeutology and concerns specific resources of pedagogical knowledge, generating personal pedagogical theories of students preparing to perform the profession of early education teacher. The celebration of the 100th anniversary of the Maria Grzegorzewska University and the celebration of the year 2022 as the Year of Maria Grzegorzewska were considered by the authors as unique opportunities to confront the thought of the patroness, her pedagogical credo contained in Letters to a Young Teacher with the reflection of contemporary young adults inspired to speak by the content of the correspondence. The direct stimulus prompting first-year preschool and early childhood pedagogy students in the 2019 and 2020 academic years to reflect on the role of the teacher was the reading of a selected Letters ...by Maria Grzegorzewska. After reading its, students wrote responses to the patroness of their university in the form of quasi-formal essays, the content of which was then analyzed to reconstruct the dominant themes. This paper presents selected results of the qualitative content analysis. The students' statements are organized according to the temporal criterion, as they report their past educational experiences, refer to the present, and also outline a vision of the anticipated role of a teacher in the future, after the stage of academic education has been completed. The main conclusions confirm the lasting vitality of pedagogical thought of the University's founder among contemporary young people. Outlined student collective portrait of the teaching profession is not overly idealized and devoid of features, hope arouses critical reflection of students on the role of the teacher in modern times